Balanced Nutrition Practice Among Mothers of Under Five Children in the Area of Bantargebang Waste Processing Site - Prasetya, Guntari; Noerfitri, Noerfitri (Universitas Padjadjaran, 2024)
Balanced nutrition is important for a mother to know and implement; hence, optimal nutritional status for the family could be achieved. Households living in the area of the waste processing site may be exposed to the environmental challenges of implementing clean and healthy living behaviors. The study aimed to analyze the relationship between knowledge, attitude, and practices of balanced nutrition among the mothers of under-five children in the area of Bantargebang integrated waste processing site. The study design was cross sectional, with 140 mothers of under-five children participating in September 2022. The data was analyzed quantitatively using descriptive and Spearman correlation test. Results showed that majority of mothers have good knowledge, attitude, and practices of balanced nutrition. There were significant correlations between mothers’ knowledge-attitude (r = 0.170; p = 0.044) and attitude-practices of balanced nutrition (r = 0.291; p = 0.0001). Mothers with good knowledge, attitudes, and practices on balance nutrition may contribute to the optimal nutritional status of the children. In conclusion, mothers’ balanced nutrition practices were correlated with their knowledge and attitude.Keywords: Balanced nutrition, clean and healthy living behavior, mother of under-five children.